A Trial Calculation Method of Complex Multi-user Electricity Charges in the Spot Market Based on Concurrent Computing Architecture - Liang, Bo; Yang, Yang; Yang, Linlin; Guo, Ke; Lu, Yuan; Wang, Suoyue (2024 7th International Conference on Energy, Electrical and Power Engineering (CEEPE), 2024)
Under the premise of the reform of the power system, the spot market has ushered in an era of vigorous development. In the face of the complex and diverse users and electricity bill settlement methods in the spot market, this study proposes a trial calculation method of complex and multi-user electricity charges in the spot market based on concurrent computing architecture. Based on the current situation of the spot market in China, this study establishes a learning model based on Apriori algorithm to explore the relationship between different electricity bill settlement packages and multiple users in the face of different types of electricity tariff calculation methods such as fixed time-sharing, tariff and hybrid and complex and diverse user categories. According to the correlation results, different electricity packages are applicable to different types of users, so the concurrent calculation method can be established to effectively improve the efficiency of electricity bill settlement.